2000
DOI: 10.1007/s002130000411
|View full text |Cite
|
Sign up to set email alerts
|

The role of corticotrophin-releasing factor in stress-induced relapse to alcohol-seeking behavior in rats

Abstract: These data suggest that CRF contributes to stress-induced relapse to alcohol seeking via its actions on extra-hypothalamic sites. The present data, and previous data with heroin- and cocaine-trained rats, point to a general role of CRF in relapse to drugs induced by stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(117 citation statements)
references
References 56 publications
8
107
1
1
Order By: Relevance
“…However, the role of other mediators of the stress response was not excluded, and pharmacological activation of the kappa system by drug injection may also affect the HPA (Iyengar et al, 1986). Corticosterone has been implicated elsewhere as a mediator in stress-induced increases in drug self-administration (Piazza et al, 1990;Deroche-Gamonet et al, 2003;Shalev et al, 2003), although other studies have suggested this hormone is either not involved (Shaham et al, 1997;Lê et al, 2000) or only indirectly involved (Erb et al, 1998). Our results showed that treatments that blocked swim stress-induced potentiation of cocaine-CPP (ie nor-BNI pretreatment, KOR gene deletion, prodynorphin gene deletion) did not block swim stressinduced increases in serum corticosterone levels.…”
Section: Discussioncontrasting
confidence: 52%
“…However, the role of other mediators of the stress response was not excluded, and pharmacological activation of the kappa system by drug injection may also affect the HPA (Iyengar et al, 1986). Corticosterone has been implicated elsewhere as a mediator in stress-induced increases in drug self-administration (Piazza et al, 1990;Deroche-Gamonet et al, 2003;Shalev et al, 2003), although other studies have suggested this hormone is either not involved (Shaham et al, 1997;Lê et al, 2000) or only indirectly involved (Erb et al, 1998). Our results showed that treatments that blocked swim stress-induced potentiation of cocaine-CPP (ie nor-BNI pretreatment, KOR gene deletion, prodynorphin gene deletion) did not block swim stressinduced increases in serum corticosterone levels.…”
Section: Discussioncontrasting
confidence: 52%
“…Reinstatement of drug seeking is also obtained with administration of the α-2 adrenoreceptor antagonist yohimbine, which, by increasing brain noradrenaline cell firing (Aghajanian and VanderMaelen 1982) and release (Abercrombie et al 1988), acts as a pharmacological stressor (Bremner et al 1996a,b;Charney et al 1983;Holmberg et al 1962;Lee et al 2004;Lê et al 2000Lê et al , 2005. These two methods were used to investigate the effect of URB597 on stress-induced alcohol seeking.…”
Section: Reinstatement Testingmentioning
confidence: 99%
“…3). The ability of stress to increase alcohol seeking (Lê et al 1998(Lê et al , 1999(Lê et al , 2000Weiss 2002a, 2003;Martin-Fardon et al 2000) is consistent with stress enhancing the probability of relapse and furthering alcohol abuse. Further, the risk of relapse in alcoholics is reportedly increased by stress (Brown et al 1990(Brown et al , 1995Pohorecky 1991;Sinha 2001), with anxiety during abstinence being a predictor of endstate drinking (Kushner et al 1994(Kushner et al , 2000(Kushner et al , 2001Sloan et al 2003;Willinger et al 2002).…”
Section: Stress During Withdrawal From Multiple Alcohol Exposures Incmentioning
confidence: 76%
“…Likewise, stress can increase alcohol-seeking behavior (Lê et al 1998(Lê et al , 1999(Lê et al , 2000Weiss 2002b, 2003;Martin-Fardon et al 2000;Weiss et al 2001). In fact, stress is a more powerful stimulus for alcohol seeking than "priming" doses of alcohol (Lê et al 1998).…”
Section: Stress During Withdrawal From Multiple Alcohol Exposures Incmentioning
confidence: 99%